The Oxford book of short stories - 20160731 frey50; Pritchett, V.S. (Oxford University Press New York, 1981)
Sir Walter Scott / The Two Drovers, Nathaniel Hawthorne/ The Birthmark, Edgar Allen Poe / The Fall Of The House Of Usher, ETC.
Keywords: Short stories -- English; Short stories -- American; Great Britain -- Social life and customs -- Fiction